Characterisation of biodiesel produced from castor oil - Mohamad Nadzrie, Lary (2014)
Ricinus communis L., or also well-known as castor bean plant which belong to Euphorbiacceae family, contain 35% - 55% of oil when extracted. This castor oil contained high value of fatty acid or ricinoleic, which make transesterification process become easier due to high solubility in methanol. Castor oil also reported slowly becoming one of valuable chemical feedstocks because of its special characteristic. Besides, production of biodiesel also gained from castor oil. Biodiesel produced from castor oil has been one of important research for current researcher. Many of them successfully produced biodiesel with several methods and different catalyst as the cheapest method still the major target. This research focus on using calcium oxide (CaO) as the catalyst which is a type of heterogeneous catalyst. Usage of heterogeneous catalyst seem to help a lot in saving the production cost. To ensure the product can be used or not, the produced biodiesel will be characterized and compare with the standards and result from previous researcher on castor oil. ASTM D6751 standards is the reference during the characterisation part take place